Penerapan Metode Active Learning dalam Meningkatkan Hasil Belajar pada Pembelajaran PAI di SMP Plus Ja-alHaq Kota Bengkulu: Penelitian - Azidnia Fauza; Desy Eka Citra Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Islamic Religious Education (PAI) learning is often considered less meaningful and too formal. Efforts to improve the quality of PAI learning can be done through the application of the Active Learning method. This study aims to determine whether the Active Learning method can improve students' understanding in PAI learning at SMP Plus Ja-alHaq and identify supporting and inhibiting factors in its implementation. The research method used is descriptive with data collection through observation, interviews, and documentation. The results of the study indicate that the application of the Active Learning method can improve students' understanding in PAI learning at SMP Plus Ja-alHaq. Students become more active in class and can understand PAI material better through interesting and not boring methods. A supporting factor in the implementation of the Active Learning method is group discussion. However, further identification of inhibiting factors is still needed. Overall, the application of the Active Learning method can be an alternative to improve the quality of PAI learning at SMP Plus Ja-alHaq.